Effect of Laser Surface Treatment on Wear Resistance of 100Cr6 Steel - Khansaa Dawood Salman (Engineering and Technology Journal, 2009)
The effect of laser surface heat treatment on wear resistance of 100Cr6 steel wasinvestigated. In this work, 100Cr6 steel which is widely used in many industrial of automobileshardened by using Nd: glass laser (l=1.060mm, t=300ms). Three different laser energies have beenused to perform hardening (0.3, 0.58 and 0.93 Joule). A pin-on-disc technique has been used toevaluate wear rate of the specimens as-received and specimens treated by Nd: glass laser atdifferent applied loads and different sliding speeds with 420 r.p.m and 45 HRC of rotatingdisc. The results show that the wear rate increases with increasing applied load and decreases withincreasing sliding speed, wear rate for laser energy 0.93 J less than another energies 0.3 and 0.5 J.Also the microhardness decreases with increasing in depth of hardening, and the microhardnessfor laser energy 0.93 J more than another energies for the same depth.